Praktik Omnibuslaw di Indonesia dilihat dari Segi Pembangunan Hukum Ekonomi - Endro Tri Susdarwono; M. Syamsul Rizal (Universitas Internasional Batam, 2021)
This study aims to describe the practice of omnibus law in Indonesia as seen from the development of economic law. This research includes normative legal research. The type of legal research is a comprehensive analytical study of primary and secondary legal materials. The results of the study are presented in a complete, detailed, clear, and systematic manner as scientific work. The approach method used is a normative juridical approach. Various studies of the relationship of law and economy show that economic progress will not be successful without the legal development that preceded it. Rules with the omnibus method reflect an integrated, codified rule where the ultimate goal is to streamline the application of these rules in practice. The practice of omnibus related to the development of economic law in Indonesia has several advantages, namely (1) changes in policies related to the economy that the Government and / or the DPR want to make will be carried out more quickly using the omnibus method, compared to amending the legislation one by one, (2) because the process is faster, this method does not require large preparation and discussion costs, (3) Omnibus law can assist the parliament in seeing the linkages between regulated provisions, so that it can provide a more comprehensive picture and therefore facilitate harmonization.